Rationality of The Bank Nagari Conversion: Perspective Analysis of â€œTigo Tungku Sajarangan â€ - Wahyudin, Rama; Wira, Ahamd; Lubis, M. Zaky Mubarak (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The dialectic of the conversion of Bank Nagari to Syariah Bank Nagari needs particular attention, especially from the point of view of rationality of thought with analysis and principles from Minangkabau traditional leaders, namely Tigo Tungku Sajarangan Â as a traditional leader who can influence certain policies. This research aims to compare the dichotomy of thoughts and principles of traditional leader Tigo Tungku Sajarangan Â regarding the pros and cons of changing the status of Bank Nagari to Nagari Islamic Bank. This research is a qualitative study with an Event Study approach. The data was collected through in-depth interviews with Tigo Tungku Sajarangan , who included traditional leaders from Penghulu, Alim Ulama and Cadiak Pandai in West Sumatra. All data were analyzed using Miles and Huberman's Interactive Qualitative data analysis model. The findings in this study indicate that the religious leaders and scholars in West Sumatra agree with the conversion process of Bank Nagari to Nagari Islamic Bank. Meanwhile, Cadiak Pandai still has disagreements, especially from political circles who occupy certain positions at the Regency or City level, and also from other figures who have roles in the scientific field who become Cadiak Clever in the Minangkabau Community area.